Implementasi Model Project Based Learning Dalam Menstimulasi Kemampuan Berpikir Kreatif Pada Kelompok B Di TK Adnyani Abiansemal Badung - Ni Kadek Intan Sukasih; Marsono Marsono; Made Gautama Jayadiningrat (Journal of Innovative and Creativity (Joecy), 2026)
The importance of creative thinking skills as part of 21st century skills that have not been optimally developed in early childhood learning. Models Project Based Learning is seen as relevant because it provides an opportunity for children to explore, imagine, and produce works independently The problems that will be discussed include the form of model implementation Project Based Learning in stimulating creative thinking skills in group B, how is the process of stimulating children's creative thinking skills through the model Project Based Learning, What are the obstacles and efforts faced by teachers when implementing the learning model Project Based Learning in stimulating the development of children's creative thinking skills in group B at Adnyani Abiansemal Badung Kindergarten. The purpose of this study is to describe and analyze the implementation of the model Project Based Learning. This research is based on the theory of creative thinking by J.P Guiford which explains the form of children's creative thinking ability, the main concept of creativity is part of thinking divergen The ability to produce various alternative solutions, John Dewey's theory of constructivism which views the process of stimulating creative ability as the main principle learning by doing. Knowledge is actively constructed by the child through real, rather than passively accepted, experience, of socio-cultural theory by Lev Vgyotsky The Implementation Learning takes place in the ZPD area (Zone of Proximal Development) through appropriate mentoring. The method used in this study is a descriptive qualitative approach Data collection techniques are carried out through observation of learning activities, in-depth interviews with teachers, principals, and parents, and documentation. The results of this study show that the implementation of Project Based Learning through the Saraswati project at Adnyani Kindergarten has proven to be effective in stimulating children's creative thinking skills. This can be seen from the active involvement of children, the diversity of ideas and works, and the development of creativity indicators. In addition, the integration of Hindu cultural and religious values in learning also contributes to shaping children's character and spiritual attitudes. These findings reinforce that contextual and meaningful project-based learning is able to develop children's potential optimally.